SENTIMENT ANALYSIS OF SERVICE PROVIDER ON TWITTER TWEET USING NAIVE BAYES CLASSIFIER WITH PHP - Juri Pebrianto (Journal of Innovation And Future Technology (IFTECH), 2023)
This study aimed to analyze the sentiments of Twitter users towards internet services provided by Indosat, Ooredoo and XL Axiata in Indonesia. Twitter Tweet data is taken using the Twitter API and processed using the PHP programming language. The classification process uses the Naïve Bayes Classifier algorithm to group positive, negative, and neutral categories. The calculation results show that negative sentiment towards Indosat Ooredoo services scores 56%, while sentiment towards XL Axiata services negatively scores 50%. The accuracy of the sentiment analysis system using PHP reaches 78% based on comparison with manual classification results. This research provides benefits in the form of information about user sentiment towards cellular internet service providers, so that each provider can improve and optimize internet services based on this data. Keywords: twitter, sentiment analysis, naïve bayes, php